Homogeneous Oxidative Coupling Catalysts: Kinetics of the Oxidation of Copper(I) Complexes [(Pyr)nCuX]4 (n = l or 2, Pyr = pyrrolidine, X = Cl, Br or I) by Dioxygen in Aprotic Media - El-Sayed, M.A.; A. Abo-El-Dahab, Hisham; H. Abd-El-Salam, Ahmed; Refaat, H. (Asian Journal of Chemistry, 2013)
This paper reports the kinetics of oxidation of [(Pyr)nCuX]4 by O2 to form the oxidative coupling catalysts [(Pyr)nCuX]4O2. The mechanism has been described as a pre-equilibrium, K, between tetranuclear copper(I) and incoming dioxygen, which is followed by rate determining step k2. The rates of the reaction are reflected to the core structure of [(Pyr)nCuX]4, faster for cubane structure as for (X = Cl or Br), when compared to step structure as in case of (X = I). The overall reaction is a second-order process, first order in each [(Pyr)nCuX]4 and [O2], with rate constant kon (kon = Kk2) and exothermic DH¹ varying from -4.9 to -15.5 kcal mol-1 and DS¹ varying from -61.3 to -97.8 cal deg-1 mol-1. kon were found to be very sensitive to n value 1 or 2.